DEVELOPMENT OF A RECEIVING-TRANSMITTING DEVICE BASED ON A CHAOTIC OSCILLATOR (Archive of Conferences, 2021)
Autogenerators are sources of primary vibrations. They applyin all radio engineering systems as exciters of transmitters, sourcesreference, reference signals and are the most critical elements [1].Dynamic chaos is a complex, disordered movement of nonlinear systems,arising in the absence of any random disturbances - since 1992attracts increased attention due to the steady trend of transition fromtheory to practice.